ICD coding for epilepsy: Past, present, and future—A report by the International League Against Epilepsy Task Force on ICD codes in epilepsy - Jette, Nathalie; Beghi, Ettore; Hesdorffer, Dale; Moshé, Solomon L.; Zuberi, Sameer M.; Medina, Marco T.; Bergen, Donna (Epilepsia (Copenhagen), 2015)
Summary The World Health Organization (WHO) International Classification of Diseases (ICD) has been used to classify causes of morbidity and mortality such as epilepsy for more than 50 years. The aims of this critical commentary are to do the following: (1) Introduce the ICD classification, summarize the ICD‐9 and ICD‐10 codes for epilepsy and seizures, and discuss the challenges of mapping epilepsy codes between these two versions; (2) discuss how the ICD‐9 and ICD‐10 relate to the revised International League Against Epilepsy (ILAE) terminology and concepts for classification of seizures and epilepsies; (3) discuss how ICD‐coded data have been used for epilepsy care and research and briefly examine the potential impact of the international ICD‐10 clinical modifications on research; (4) discuss the upcoming ICD‐11 codes and the role of the epilepsy community in their development; and (5) discuss how the ICD‐11 will conform more closely to the current ILAE terminology and classification of the epilepsies and seizures and its potential impact on clinical care, surveillance, and public health and research.